'A lock so tallying in all its parts, that any part of one lock may fit another': exploring the standardisation and interchangeable manufacturing of New Land Pattern Musket Locks. (2nd January 2021) - Williams, David; Abbott, Philip; Harding, David
Abstract : A Select Committee Report of 1817 states that the New Land Pattern Musket has 'a lock so tallying in all its parts, that any part of one lock may fit another'. This is the earliest claim of interchangeability to have been found for Board of Ordnance firearms. It has focussed the authors' attention on understanding the British efforts in the interchangeable manufacturing of firearms in the early 19th century, and more specifically on the manufacture of the lock of the New Land Pattern Muskets. This has also necessitated and included some work to unravel the story of the development of the New Land Pattern Musket and its variants, and to appreciate the contemporary use of lock jiggers by the East India Company (EIC) and others. Our approach has blended multiple iterations of archival research, object study, analysis of musket lock 'Types', and experimental evaluations of interchangeability. The methods used have allowed a comparison with contemporary American achievements at the Springfield and Harpers Ferry National Armories. This paper reports our results, including those of a close study of 35 New Land Pattern Muskets; the generation of a typology identifying three distinct variants of New Land Pattern Musket locks and a chronology of key aspects of their design, manufacture and supply; a five-lock component exchange experiment with 20 potential interchanges and other supplementary interchange tests; and an experimental evaluation of the use of two surviving EIC lock jiggers (i.e. gauges). These demonstrate that Great Britain had made significant strides in the interchangeable manufacturing of musket locks by 1817, but that these achievements, based upon the use of gauges and other similar tooling, were limited by their use of manual methods, chiefly filing by hand. They also show that Henry Nock, Ezekiel Baker and others contributed to the design of the variants of the musket, the lock and the tooling. The work also indicates that Britain was attempting interchangeable lock manufacturing in more than one geographical location, at the workshops of key suppliers in Birmingham and the Black Country (the metal working district to the West and North West of Birmingham), the London trade and the new Royal Manufactory in Lewisham. This multiple site approach would have been particularly challenging, and it is also important to note that much of this work was carried out in time of war. These British innovations may have influenced others through the transfer of technology by former Ordnance artificers, including at the Imperial Manufactory at Tula in Russia via John Jones, father and son. The experimental comparison with contemporary American achievements shows that the British were realising levels of interchangeability at least equivalent to those at US National Armories, but that whilst the dimensional control sought in Britain may have been less demanding it was being attempted at many more sites.